From Micro Financial Statementes to Macro Accounting: an Integrated Model Based on the Measurement Approach (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
The nomenclature in National, Public, and Financial Accounting, while sharing a common noun, has yet to explore potential synergies. Despite accounting's capacity for powerful analysis at micro and macro levels, the persistent microaccounting-macroaccounting dichotomy limits these synergies. Despite modest reception, scholars have explored converging Accounting into a comprehensive discipline, emphasizing interconnections between macro and micro levels. This study presents a conceptual model spanning micro, meso, and macro fundamental accounting identities. Employing abstract concepts like Dichev and Tang (2008), Dichev (2008, 2017), and Miller & Bahnson (2010), it organizes economic value stocks and flows from micro to macro levels. Aligned with Scott's concept of accounting under ideal conditions (2015), it's grounded in Beaver's Measurement Approach (1989). The study confirms, through micro accounting consolidation, that only real assets constitute society's concrete capital. It outlines cyclic dynamics of rental phenomena from diverse assets, accruing rental values at each aggregation level. This analytical approach aids understanding accounting's nature and identifies avenues for future research, including empirical estimation and periodic reassessment of abstract categories.